2009
DOI: 10.1007/s00395-009-0055-x
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional regulation of Pim-1 kinase in vascular smooth muscle cells and its role for proliferation

Abstract: The Ser/Thr-protein kinase Pim-1 has been discovered as a novel transducer of survival- and cell cycle promoting signals in the hematopoietic cell system. Although its significance for proliferation of vascular smooth muscle cells (VSMC) in vitro and neointima formation in vivo has been suggested recently, the mechanism has barely been characterized. This study aimed to foster the understanding of Pim-1 expression and regulation in murine VSMC in response to factors typically present within the atherosclerotic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
36
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 49 publications
6
36
0
Order By: Relevance
“…Western blot analysis was performed as described previously [31] using the following antibodies and dilutions: mouse monoclonal anti-HIF-1a (BD Biosciences, Germany) 1:500; rabbit polyclonal anti-HIF-2a (Novus Biologicals, USA) 1:1,000; rabbit polyclonal HIF-3a (ab10134, Abcam, UK) 1:1,000; mouse anti-b-actin (Santa Cruz, USA) 1:1,000; sheep anti-mouse-HRP (GE Healthcare, USA) 1:10,000; goat anti-rabbit-HRP (Santa Cruz, USA) 1:2,500. Intensities of protein bands were estimated with ''Quantity One'' software from BioRad (USA).…”
Section: Western Blot Analysismentioning
confidence: 99%
“…Western blot analysis was performed as described previously [31] using the following antibodies and dilutions: mouse monoclonal anti-HIF-1a (BD Biosciences, Germany) 1:500; rabbit polyclonal anti-HIF-2a (Novus Biologicals, USA) 1:1,000; rabbit polyclonal HIF-3a (ab10134, Abcam, UK) 1:1,000; mouse anti-b-actin (Santa Cruz, USA) 1:1,000; sheep anti-mouse-HRP (GE Healthcare, USA) 1:10,000; goat anti-rabbit-HRP (Santa Cruz, USA) 1:2,500. Intensities of protein bands were estimated with ''Quantity One'' software from BioRad (USA).…”
Section: Western Blot Analysismentioning
confidence: 99%
“…Such research has thus far been conducted in the hematopoietic cell system (Mikkers et al 2004;Stout et al 2004) and vascular cells (Willert et al 2010), where signal transduction for the initiation of Pim-1 transcription is followed by cytokine stimulation. In this study, SS mediated a long-term effect on the induction of Pim-1 in rat MSCs for at least 12 h, demonstrating that the increase in Pim-1 gene expression level induced by SS was not transient.…”
Section: Discussionmentioning
confidence: 99%
“…Several reports have suggested that MAPKs can modulate the expression of Pim-1 (Aksoy et al 2007;Hu et al 2009;Willert et al 2010). It has also been reported that fluid flow activates MAPKs (Fitzgerald et al 2008;Wu et al 2006).…”
Section: Involvement Of the Mapk Pathways In Ss-induced Pim-1 Expressionmentioning
confidence: 97%
See 1 more Smart Citation
“…More and more evidence has demonstrated that Pim-1, a proto-oncogene encoding a serine/threonine protein kinase, plays an essential role in cell survival, cell proliferation, cell differentiation, cell cycle, and cell apoptosis (7)(8)(9)(10)(11)(12)(13)(14), especially in the occurrence and development of tumors (15)(16)(17)(18)(19)(20). Therefore, the rapidly increasing knowledge on the role of the Pim-1 in cancer will hopefully provide useful molecular markers for detection and prognosis of tumor.…”
Section: Introductionmentioning
confidence: 99%